2015
DOI: 10.1111/hpb.12373
|View full text |Cite
|
Sign up to set email alerts
|

Are sarcopenia, obesity and sarcopenic obesity predictive of outcome in patients with colorectal liver metastases?

Abstract: Sarcopenia, obesity and sarcopenic obesity did not worsen DFS, OS and complication rates after a partial liver resection for CRLM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
99
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 36 publications
4
99
2
1
Order By: Relevance
“…However, in a recent study, neither sarcopenia nor sarcopenic obesity was found to have an impact on survival after liver resection for CRC liver metastases [4]. In the same report, excessive body fat, estimated from measurements of skeletal mass areas on available computed tomography scans and body weight, correlated with improved overall and diseasefree survival [4], which is in accordance with our findings. On the other hand, among surgical patients those at the extremes of BMI (underweight and morbidly obese) have the highest postoperative mortality, which persists at long term [27].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, in a recent study, neither sarcopenia nor sarcopenic obesity was found to have an impact on survival after liver resection for CRC liver metastases [4]. In the same report, excessive body fat, estimated from measurements of skeletal mass areas on available computed tomography scans and body weight, correlated with improved overall and diseasefree survival [4], which is in accordance with our findings. On the other hand, among surgical patients those at the extremes of BMI (underweight and morbidly obese) have the highest postoperative mortality, which persists at long term [27].…”
Section: Discussionsupporting
confidence: 91%
“…Despite some inconsistency in the literature [4,9,10], several articles have shown an increased risk for perioperative complications in obese patients undergoing hepatectomy [2,5e7]. In our cohort, neither obesity nor diabetes was identified as a major predictor of perioperative morbidity or mortality.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Peng et al reported an increase in severe post-operative complications in patients with colorectal cancer with sarcopenic obesity who underwent hepatic resection (18). However, Lodewick et al reported that sarcopenia and sarcopenic obesity did not impact complication rates in a similar study population (19). A meta-analysis of 14 studies linking sarcopenic obesity to clinical outcomes in cancer patients concluded that sarcopenic obesity was associated with increased surgical complications (14).…”
Section: Discussionmentioning
confidence: 99%
“…Predefined cutoffs were adopted in 8 studies [11,20,[24][25][26][27][28]39], and optimum stratification, receiver operator characteristic curve and study-specific percentiles were used in the other studies [12-14, 21-23, 29-38, 40-42]. Sex-specific cutoffs were employed in almost all of the included studies, and on comparison with males, females showed a relatively lower muscle mass and MA (Table 3).…”
Section: Cutoff For the Sarcopenia Indexmentioning
confidence: 99%